Neonatal Pain Management: Is There An Endocrinal Response? - Elfarargy, Mohamed Shawky; Ahmad, Ahmad Roshdy; Elbadry, Dalia Hamdy (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2025)
Neonates exhibit pain responses characterized by various endocrinal changes, including alterations in cortisone and oxytocin serum levels, as well as physiological and emotional reactions. The administration of neonatal pain management leads to the normalization of endocrine hormones, including cortisone and oxytocin, which are affected by the presence of neonatal pain. Diagnosing neonatal pain is complex; however, effective management is essential. An adequate balance should be established between the analgesics used for pain management and their associated side effects. Uncontrolled neonatal pain is correlated with delayed development with increased neurologic insult. This review aims to examine the significance of neonatal pain, along with its clinical and physical manifestations. It also explores strategies for managing neonatal pain, encompassing both pharmacological and non-pharmacological methods, along with the particular medications utilized in pharmacological interventions. This discussion includes various non-pharmacological methods for managing neonatal pain. Additionally, this review examines methods for pain assessment. The aim is to highlight the significance of pain in this vulnerable population and to promote the implementation of diverse management strategies for neonatal pain to prevent serious yet avoidable, adverse effects in neonates.
Keywords: analgesic drugs